Persepsi Penyintas Covid-19 terhadap Stigma Sosial Masyarakat dan Pengaruhnya pada Interaksi Sosial Penyintas Covid-19 di Kota Banjarmasin - Asiah, Nor; Imadduddin, Imadduddin (Jurnal Al-Husna, 2024)
One of the impacts of COVID-19 is the emergence of stigma against people who are positive for COVID-19. Stigma is a term that describes a situation or condition related to the point of view of something that is considered negative. This research uses quantitative methods and is processed by statistical analysis methods. The method used is the correlational method, then in this study the researcher used a purposive sampling technique. Based on the results of the study, the results showed that: In general, social interaction among COVID-19 survivors in Banjarmasin City was moderate. The results of the hypothesis test are clearly known that there is a significant contribution of 0.000 between the perception of stigma on social interaction in COVID-19 survivors in Banjarmasin City, with an effective contribution of 52.1%. Based on the data obtained from data analysis with the SPSS 23.0 software program for windows, the significance value or p value is 0.000. It is said to be significant if p < 0.05. So the results found are significant, so the hypothesis (Ha) that there is an influence of stigma perception on social interaction in COVID-19 survivors in Banjarmasin City is accepted, meaning that the stigma perception variable affects the social interaction variable.